1987
DOI: 10.1093/ajcn/45.3.588
|View full text |Cite
|
Sign up to set email alerts
|

Insulinemic and glycemic indexes of six starch-rich foods taken alone and in a mixed meal by type 2 diabetics

Abstract: The glycemic index concept neglects the insulin secretion factor and has not been systematically studied during mixed meals. Six starch-rich foods were tested alone and in an isoglucido-lipido-protidic meal in 18 NIDDs and compared with a glucose challenge. These test meals were randomly assigned using a three factor experiment design. All three tests contained 50 g carbohydrate; mixed meals were adjusted to bring the same amount of fat (20 g), protein (24 g), water (300 mL), and calories (475 kcal) but not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(99 citation statements)
references
References 31 publications
10
86
2
1
Order By: Relevance
“…However, the glycemic index values for white bread ranged from 44 to 132, with a CV of 30%. This value is consistent with the calculated CVs from other reports with healthy volunteers, which ranged from 12 to 53% (3,(15)(16)(17). From a report evaluating the glycemic response to white bread (18), the mean among-subject CV for the AUC was calculated as 33% for subjects with type 2 diabetes and 39% for subjects with type 1 diabetes.…”
Section: Conclusion -D E S P I T E T H Esupporting
confidence: 88%
“…However, the glycemic index values for white bread ranged from 44 to 132, with a CV of 30%. This value is consistent with the calculated CVs from other reports with healthy volunteers, which ranged from 12 to 53% (3,(15)(16)(17). From a report evaluating the glycemic response to white bread (18), the mean among-subject CV for the AUC was calculated as 33% for subjects with type 2 diabetes and 39% for subjects with type 1 diabetes.…”
Section: Conclusion -D E S P I T E T H Esupporting
confidence: 88%
“…In a study of eight healthy subjects [70], there were substantial differences in insulin responses to six mixed meals with various GI values, and insulin response correlated well with the glycaemic response (r = 0.83). Similarly, it was found that GI values were useful in discriminating glycaemic and insulinaemic responses of mixed meals among diabetic patients [73]. A recent crossover study of 12 obese teenage boys found that a low GI meal led to lower plasma glucose and insulin response [74].…”
Section: Dietary Carbohydrate and Type II Diabetesmentioning
confidence: 97%
“…The study demonstrated that, in respect to glucose-raising potential, the hierarchy between foods tested alone (GI testing) was respected once the same foods were tested in these meals. This means that the GI concept remains discriminating in the context of a meal (Bornet et al 1987).…”
Section: Glycaemic Index Of Mixed Mealsmentioning
confidence: 99%